2009
DOI: 10.1111/j.1365-2265.2009.03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of insulin resistance with anti‐Mullerian hormone levels in women without polycystic ovary syndrome (PCOS)

Abstract: An independent relationship exists between HOMA-IR and AMH in women without PCOS, possibly due to the effect of abnormal insulin action on AMH secretion by granulosa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 42 publications
10
58
4
Order By: Relevance
“…However, the small number of subjects in this study, differences in study populations and clinical setting must all be taken into consideration. The purported relationship between insulin resistance and metabolic syndrome with AMH has been a source of controversy [26,29]. In our study, AMH was not related to insulin resistance-or metabolic syndrome-related variables, irrespective of the PCOS status, and is in agreement with other studies [8,11].…”
Section: Discussionsupporting
confidence: 82%
“…However, the small number of subjects in this study, differences in study populations and clinical setting must all be taken into consideration. The purported relationship between insulin resistance and metabolic syndrome with AMH has been a source of controversy [26,29]. In our study, AMH was not related to insulin resistance-or metabolic syndrome-related variables, irrespective of the PCOS status, and is in agreement with other studies [8,11].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we evaluated fasting insulin levels as a measure for insulin resistance and related these to ovarian reserve markers. The negative association between fasting insulin levels and AMH was previously described in the reproductive-age women without PCOS (16) and was confirmed by our study among CCS.…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, no other studies that assess a possible link between obesity and AMH have been performed in female CCS. In the general population, only one study among three has shown an association in women of reproductive age (15,16,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the evaluation of the relationship between AMH concentrations and BMI generally showed contradictory results. In some studies [14,15] a significant inverse association between AMH levels and BMI was found, whereas some others [16][17][18][19] found no relationship between AMH and BMI.…”
Section: Introductionmentioning
confidence: 95%